2009 IEEE Power &Amp; Energy Society General Meeting 2009
DOI: 10.1109/pes.2009.5275850
|View full text |Cite
|
Sign up to set email alerts
|

Progress report on natural esters for distribution and power transformers

Abstract: Natural ester seed oil based dielectric fluid is an environmentally advantaged fluid that is increasingly being used as a replacement for mineral oil and for high temperature flashpoint liquids, including silicone and R-TEMP. This report updates experience with use of the fluid over the last two years. Considerable studies have been conducted to investigate heat aging performance of cellulose, electrical contact thermal stability, dielectric strength, moisture sensitivity, and cold temperature performance. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…For years, various research works were carried out on different aspects such as on the safety / environmental, ageing and electrical performances of the vegetable oil [2][3][4][5][6][7][8][9][10][11][12]. Vegetable oil such as natural ester was also successfully applied in-service where it was used from small to medium transformers up to a voltage level of 66 kV [11]. Among the attractive factors of vegetable oil is the non-toxicity and highly biodegradable which ensure low risk to the environment if there is a spillage.…”
Section: Introductionmentioning
confidence: 99%
“…For years, various research works were carried out on different aspects such as on the safety / environmental, ageing and electrical performances of the vegetable oil [2][3][4][5][6][7][8][9][10][11][12]. Vegetable oil such as natural ester was also successfully applied in-service where it was used from small to medium transformers up to a voltage level of 66 kV [11]. Among the attractive factors of vegetable oil is the non-toxicity and highly biodegradable which ensure low risk to the environment if there is a spillage.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis using the Microsoft Office Excel 2003 and OriginPro v.8.6 software packages has shown that the data is normally distributed allowing calculation of the standard deviation of the breakdown voltage and this has been used to estimate the 1, 10, 50 and 90% breakdown probability for each liquid. This data is relevant to the design of power and pulse power equipment, [5][6][7][8][9][10][11], as it affects safety-margin design requirements for liquid-insulated, high-voltage equipment. Values of the effective mobility of the charge carriers in the liquids were obtained from pre-breakdown I-V characteristics, measured in a point-plane electrode topology, following the procedure reported in [12].…”
Section: Introductionmentioning
confidence: 99%
“…For many years, various research works were carried out on different aspects such as safety/environmental, ageing and electrical performance of vegetable oil. Transformer filled with vegetable oil were already tested successfully at different voltage level [1]. Among the attractive factors of vegetable oil is the non-toxicity and highly biodegradable, which ensure low risk to the environment if there is a spillage.…”
Section: Introductionmentioning
confidence: 99%